International marketing strategies of emerging market firms: Nature, boundary conditions, antecedents, and outcomes. Issue 2 (9th April 2018) - Boso, Nathaniel; Debrah, Yaw A.; Amankwah-Amoah, Joseph
Abstract : Purpose: The purpose of this paper is twofold: to publish scholarly works that extend knowledge on the drivers, consequences and boundary conditions of international marketing strategies employed by emerging market firms of all sizes and types; and to advance a narrative for future research on emerging market firms' international marketing activities. Design/methodology/approach: To achieve this agenda, the authors invited scholars to submit quality manuscripts to the special issue. Manuscripts that addressed the special issue theme from varied theoretical perspectives and methodological approaches were invited. Findings: Out of 70 manuscripts reviewed, 7 are eventually accepted for inclusion in this special issue. The papers touched on interesting research topics bothering on international marketing practices of emerging market firms using blend of interesting theoretical perspectives and variety of methods. Key theoretical perspectives used include resource-based theory, internationalization theory, institutional theory and corporate visual identity theory. The authors employed unique sets of methods including literature review, surveys, panel data, and process-based qualitative and case-study enquiries. The authors used some of the most advanced analytical techniques to analyze their data. Originality/value: This introduction to the special issue provides a review of the extant literature on the international marketing strategy of emerging market firms, focusing on summarizing key empirical contributions on the topic over the last three decades. Subsequently, the authors discuss how each paper included in this special issue helps advance the agenda to develop scholarly knowledge on emerging market firms' international marketing strategy.